Demand for crop genetic resources and the US National Plant Germplasm System - Day-Rubenstein, Kelly; Smale, Melinda; Widrlechner, Mark P. (Wiley, 2006)
Although genetic resources have strong public-goods characteristics, public genebanks often have struggled for adequate funding. A review of economic literature on the value of plant genetic resources indicated that more information is needed about germplasm use. The data compiled in this paper examine patterns of germplasm use for one of the world's largest national genebank networks, the U.S. National Plant Germplasm System (NPGS). Data on 10 major crops, gathered directly from within the NPGS and from end-users, revealed patterns of usage for germplasm during the period from 1995 to 1999. Data were collected describing the characteristics of NPGS users, the types of germplasm requested, the purpose of requests, and, when applicable, the specific traits sought. From these findings, we estimated the utility of distributed materials, their secondary use, and projected future demand for NPGS resources. To explore relationships between the usefulness of germplasm samples and accompanying data in a more systematic fashion, we estimated a linear regression. The regression model suggests that accompanying data make germplasm more useful. We conclude that demand for NPGS resources was substantial and came from broad range of users. Utilization rates were higher than suggested by past studies. Countries with developing economies made greater use of NPGS resources, relatively speaking, than did countries with high-income economies. Finally, demand for NPGS resources is likely to increase, especially among users in countries with developing economies.